Need and Use of Performance Indicators in State Transport Undertakings : A Case Study of Pepsu Road Transport Corporation - Goyal, Munish; Bansal, S.K. (Gyan Management Journal, 2009)
The study attempts to highlight the need for restructuring policies ofstate transport undertakings to improve their efficiency. Furthermore, it emphasizes the need of making use of various performance indicators which may help STUs to formulate an appropriate strategy to achieve their economic and social goals.
Keywords: Pepsu Road Transport; State Transport Undertakings {STUs)